TYPES AND FUNCTION OF SATIRE IN RONNY CHIENG’S STAND-UP COMEDY PERFORMANCE: AMERICA NEEDS MORE ASIANS (2019) AND EVERYTHING’S STUPID (2020) - Mauritania H Subagyo; Sari Rejeki; Agnes Setyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
The purpose of this research is to analyze types and functions of satire used in two of Ronny Chieng’s stand-up comedy performances; America Needs More Asians (2019) and Everything’s Stupid (2020). This study uses descriptive qualitative method with observation and note-taking technique. The analysis show that the types of satire found in the utterances of Ronny Chieng are; satire (15), cynicism (7), sarcasm (3), and innuendo (2).  The satire functions as ridiculing of thoughts and ideas, sarcasm, laughing at ideas and habits and understating facts. Satire is used in the stand-up comedy as a critic, specifically for Caucasians, African Americans and Asians.Keywords: satire, type and function, stand-up comedy